PENGABDIAN MASYARAKAT PEMBERIAN EDUKASI TENTANG SANITASI LINGKUNGAN DI DINAS KOPERASI DAN UKM KABUPATEN PALI - Achmad Allfaress, Reffky; Wati, Nopia; Ramon, Agus; Kosvianti, Emi (Gayaku Publisher, 2024)
Environmental sanitation is aimed at creating a safe and comfortable place, by making efforts to prevent disease in order to realize good environmental quality in terms of physical, chemical, biological and social. This research discusses the sanitation of public places, one of which is the workplace. The workplace is a place that does not escape the reach of the community. One of the scopes of the workplace is the workspace and work facilities for employees in the office, this is usually reached by office employees, therefore, the importance of knowledge about sanitation needs to be considered, especially for employees and cleaning service (janitors) in the office. This activity was carried out at the Office of Cooperatives and SMEs located on Jalan Taman Siswa RT. 02, RW 01 Kelurahan Talang ubi selatan, Kecamatan talang ubi, Kabupaten PALI, which aims to increase the knowledge and level of public awareness about the importance of maintaining sanitation in the office environment and build direct interaction between office employees and cleaning service officers. The activities carried out in the form of providing education to employees and cleaning service officers at the Cooperative and SME Office. The expected results of this activity are that it can provide knowledge to the community, especially in the application of sanitation and maintaining the cleanliness of the office environment, reducing disease transmission and the formation of cooperation between office employees and cleaning service officers in realizing a healthy work environment.